Penerapan Kualitas Pelayanan Room Attendant pada Kepuasan Tamu di Hotel Montana Kota Malang - Brigita Yvonne Carmelia; Hapsa Sopalatu; Muhammad Danang Setioko (University of Merdeka Malang, 2023)
Hotel Montana is one of the hotels located in the center of Malang City, and is a popular accommodation for tourists. This study aims to determine and analyze the effect of room attendant service quality on guest satisfaction at Hotel Montana Malang City. Writing This research uses a quantitative method with a descriptive approach. The population in this study were all guests staying at the Hotel Malang, while the sample in this study was determined using the slovin formula. Data collection techniques in this study used a questionnaire (questionnaire) given to respondents. Data analysis techniques in this study used validity and reliability tests, simple linear regression tests and hypothesis testing. From the results of this study it can be concluded that service quality influences guest satisfaction staying at the Montana Hotel in Malang City intentions.